The Human Rights Council in the new international order and the new mechanisms of revision (Polis (Santiago), 2018)
This paper analyzes the Human Rights topic under a multilateral policy perspective. In this regard, it focuses on the innovations that have entailed the establishment of the Human Rights Council, instead of the former Human Rights Commission. For that purpose, special emphasis is placed on the study of political discussions within the International Community, during the process of establishment of the new Council, as well as the new review mechanisms that it contemplates.
Keywords: multilateralism; United Nations; human rights commission; human rights council